Question 1 of 5Find the Inverse of each Function
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=-\frac{x}{2}$$
B
$$f^{-1}(x)=-\frac{2}{x}+2$$
C
$$f^{-1}(x)=x+\frac{1}{x}$$
D
$$f^{-1}(x)=\frac{2-x}{2}$$
E
$$f^{-1}(x)=-\frac{2+x}{x}$$
Question 2 of 5Find the Inverse of each Function
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=\frac{2x-3}{8}$$
B
$$f^{-1}(x)=-\frac{12x}{8+3x}$$
C
$$f^{-1}(x)=\frac{-3x+12}{8}$$
D
$$f^{-1}(x)=12+\frac{8}{3x}$$
E
$$f^{-1}(x)=8x-\frac{1}{4}$$
Question 3 of 5Find the Inverse of each Function
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=(x-1)^5-2$$
B
$$f^{-1}(x)=\frac{-2}{(x-1)^5}$$
C
$$f^{-1}(x)=\frac{(x+1)^5}{2}$$
D
$$f^{-1}(x)=-2+(x+1)^5$$
E
$$f^{-1}(x)=1-\frac{1}{\sqrt[5]{x+2}}$$
Question 4 of 5Find the Inverse of each Function
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=\sqrt[3]{x-2}-2$$
B
$$f^{-1}(x)=\frac{2}{\sqrt[3]{x+3}}$$
C
$$f^{-1}(x)=\sqrt[3]{x+8}+64$$
D
$$f^{-1}(x)=\sqrt[3]{x+8}-64$$
E
$$f^{-1}(x)=\frac{2}{\sqrt[3]{x+64}}$$
Question 5 of 5Find the Inverse of each Function
Select the Correct Answer Below: Correct! Not Correct!
A
$$f^{-1}(x)=\sqrt[5]{\frac{2}{x+1}}$$
B
$$f^{-1}(x)=\frac{(x+1)^5}{2}$$
C
$$f^{-1}(x)=\frac{2}{(x+1)^5}$$
D
$$f^{-1}(x)=\sqrt[5]{\frac{x+1}{2}}$$
E
$$f^{-1}(x)=\frac{\sqrt[5]{2}}{(x+1)^5}$$

Great Job! You Passed!

Better Luck Next Time...

Restart Quiz ↻
Review Lesson ↻
Next Lesson »